Role of Social Presence in Mediating Learning Satisfaction in Online Learning - Edy Suryanto; Nina Oktarina; Tusyanah Tusyanah (Journal of Learning for Development, 2024)
This study was intended to determine the effect of interaction, self-regulation and course structure on student satisfaction through social presence. This research adopted a quantitative research approach. The sample of this study consisted of 187 higher education students of Economics Education in Universitas Negeri Semarang based on the proportional random sampling technique. Data was collected using a questionnaire which was then analysed through the Structural Equation Model (SEM) approach using the Smart PLS version 3.0 application. This research concluded that interaction and self-regulation and mediating variables social presence succeeded in influencing student satisfaction. In contrast, the course structure was found not to affect student satisfaction, and social presence failed to mediate self-regulation variables on student satisfaction. It is recommended that lecturers design an interactive learning environment by considering student characteristics. The balance between structure and dialogue was a determining factor for student satisfaction, so the design that was prepared is expected to facilitate students to be actively involved and achieve satisfaction.